The Influence Of Digital Marketing & Innovasion On The School Performance - et. al., Yanti Purwanti, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze the effect of digital marketing on school performance, the influence of innovation on school performance and the influence of digital marketing on school performance. The analytical method used in this research is structural equation modeling (SEM) to determine the causal relationship between latent variables contained in structural equations. The analysis tool used is with the help of Smart PLS. The method used in this research is quantitative methods, data collection methods by distributing questionnaires to the teacher. The results of the questionnaire returned were 150 respondents. Based on the results of data analysis, it is concluded that innovation has a significant effect on teacher performance, digital marketing has no significant effect on teacher performance, digital marketing has a significant effect on innovation.